2021
DOI: 10.1002/pbc.28437
|View full text |Cite
|
Sign up to set email alerts
|

Psychosexual functioning in cancer survivorship: What the pediatric oncologist needs to know

Abstract: Sexual health may be disrupted in adolescents and young adults (AYAs) both during and after cancer treatment, irrespective of whether they are diagnosed in childhood, adolescence, or young adulthood. Unfortunately, oncology providers often underestimate the relevance of psychosexual issues for AYAs and underprioritize sexual health throughout treatment and survivorship. The purpose of this narrative review is to provide information on (a) the etiology of psychosexual dysfunction in childhood, adolescent, and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 91 publications
(219 reference statements)
0
5
0
Order By: Relevance
“…2 Physicians can help address this issue by being proactive in addressing the topic. Psychosexual complications in survivorship are addressed in more detail in the special edition article by Fredericks et al 61…”
Section: Fertility-related Psychosocial and Psychosexual Functioningmentioning
confidence: 99%
“…2 Physicians can help address this issue by being proactive in addressing the topic. Psychosexual complications in survivorship are addressed in more detail in the special edition article by Fredericks et al 61…”
Section: Fertility-related Psychosocial and Psychosexual Functioningmentioning
confidence: 99%
“… 14 Identifying team members, such as nurses, social workers, psychologists, sexologists, physician assistants, and physical therapists who have the proper experience and skills to communicate about sexual health with AYAs, may improve the likelihood of counselling is offered, and reduce the burden of time from the oncologist. 6 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a previous survey, 50% of pediatric oncologists expressed the need for further education on sexual function and gender identity/sexual orientation, and more than 30% reported a need for more education on body image, sexual activity/safe sex practices, and contraception. 6 On the other hand, several studies demonstrated an overall lack of medical knowledge about LGBTQ patient health care and highlighted the need for more education among oncology healthcare providers. 21-24 Improving clinician knowledge on gender identities and sexual orientation and how sexual health needs may differ is an important step in ensuring all conversations are inclusive and may reduce professional discomfort during sexual health communication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations